2021
DOI: 10.1038/s41598-020-79987-4
|View full text |Cite
|
Sign up to set email alerts
|

Low retinoic acid levels mediate regionalization of the Sertoli valve in the terminal segment of mouse seminiferous tubules

Abstract: In mammalian testes, undifferentiated spermatogonia (Aundiff) undergo differentiation in response to retinoic acid (RA), while their progenitor states are partially maintained by fibroblast growth factors (FGFs). Sertoli valve (SV) is a region located at the terminal end of seminiferous tubule (ST) adjacent to the rete testis (RT), where the high density of Aundiff is constitutively maintained with the absence of active spermatogenesis. However, the molecular and cellular characteristics of SV epithelia still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…In fact, at least three FGFs, including FGF2, FGF4 and FGF8 among others that found in the RT fluid (Cotton et al 2008 ). A very recent study reported that the RT epithelium expresses FGF9 and FGF10 (Imura-Kishi et al 2021 ). These other factors may also be necessary for normal development of the RT.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at least three FGFs, including FGF2, FGF4 and FGF8 among others that found in the RT fluid (Cotton et al 2008 ). A very recent study reported that the RT epithelium expresses FGF9 and FGF10 (Imura-Kishi et al 2021 ). These other factors may also be necessary for normal development of the RT.…”
Section: Discussionmentioning
confidence: 99%
“…Using a transgenic system of Sertoli cell ablation, Imura-Kishi et al 2021 showed that donor Sertoli cells first colonize the transitional zone where they resume repression of spermatogenesis. After reaching an equilibrium in the transitional zone Sertoli cells then proliferate further, repopulating the host seminiferous epithelium where the donor Sertoli cells will support host spermatogenesis ( 88 ).…”
Section: Sertoli Cell Transplantation and Transitional Zone Sertoli C...mentioning
confidence: 99%
“…Loss of AR has been shown to inhibit Sertoli cell maturation ( 106 ). In men and rodents, germ cells that reside in this region are exclusively spermatogonia that seem to be predominantly undifferentiating spermatogonia ( 88 , 92 , 99 , 107 ). Collectively the transitional zone represents a unique Sertoli-germ cell niche within the testis.…”
Section: Sertoli Cell Transplantation and Transitional Zone Sertoli C...mentioning
confidence: 99%
“…The researchers transplanted labeled SCs obtained from the convoluted seminiferous tubules of mice (C57BL/6-R26-H2B-mCherry) into the testes of recipient mice (C57BL/6-Tg AMH-Treck, Shinomura et al, 2014), whose SCs were previously destroyed by injection of diphtheria toxin. At 45 days after transplantation, donor SCs formed new TZs in the terminal segments of the recipient's seminiferous tubules, stained positive for this zone markers p-AKT (RAC-alpha serine/threonine-protein kinase, Protein kinase B alpha, Imura-Kishi et al, 2021) and ace-Tub (acetylated form of tubulin, Aiyama et al, 2015;Imura-Kishi et al, 2021) and highly expressed GDNF, as is the norm.…”
Section: Functions Of the Adult Mousementioning
confidence: 99%
“…While the biology of SSCs and SCs, as well as the entire process of male germ cell development, have been sufficiently studied and covered in many reviews (Griswold, 1998;Griswold, 2018;Hess and Renato de Franca, 2008;Kopera et al, 2010;Kubota and Brinster, 2018;de Rooij, 2017), the development of rete testis and understanding of its role in the functioning of the spermatogenic system are only beginning to gain clarity. Recently, a study (Imura-Kishi et al, 2021) revealed the role of the rete testis in maintaining the regional specialization of the SCs in the terminal sections (transitional zones) of the convoluted seminiferous tubules. Evidence suggests that the terminal sections of the seminiferous tubules are a niche for Gfra1 + SSCs (Aiyama et al, 2015), the site of the prolonged proliferation of SCs in the pubertal and postpubertal testis (Figueiredo et al, 2016(Figueiredo et al, , 2019Malolina and Kulibin, 2017), and the site of spermatogenic wave generation that supports conti-…”
mentioning
confidence: 99%